PENGARUH PROFITABILITAS, SOLVABILITAS, DAN REPUTASI KANTOR AKUNTAN PUBLIK TERHADAP AUDIT DELAY DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL PEMODERASI - Edianto, Edianto (Jurusan Akuntansi FEB UNTAN, 2025)
This research aims to examine the influence of Profitability, Solvency, and Public Accountant Office Reputation on audit delay with Company Size as a moderating variable in Property and Real Estate Companies listed on the Indonesia Stock Exchange during the years 2020-2022. The sample consists of 52 companies over a period of 3 years, resulting in a total of 156 research samples. Purposive sampling was employed as the research method. Hypothesis testing was conducted using multiple regression analysis and moderated regression analysis with the assistance of SPSS software version 25. The research findings indicate that Profitability has a negative influence on audit delay, while Solvency and Public Accountant Office Reputation do not affect audit delay. Company Size does not moderate the influence of Solvency and Public Accountant Office Reputation on audit delay. Conversely, Company Size is able to moderate the influence of Profitability on audit delay.